EFEKTIVITAS KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DI KELAS X TAV SMK NEGERI 1 BATANG ANGKOLA - SITI HALIJAH LUBIS (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2019)
ABSTRACT This study aims to describe the effectiveness of students’ critical thinking ability by using cooperative learning model of Jigsaw type at the tenth grade students of TAV major of SMK Negeri 1 Batang Angkola. The research was conducted by using quasi experimental method (pretest post test one group design) with 36 students as the sample and they were taken by using cluster random sampling technique from 94 students. Test and questionnaire were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using Jigsaw type was 3.80 (good category), (b) the average of students’ critical thinking ability before using Jigsaw type was 53.83 (fair category) and after using Jigsaw type was 87.84 (very good category). Furthermore, based on inferential statistic by using paired sample ttest and helping SPSS version 16, the result showed the significant value was less than 0.05 (0.000<0.05). It means, there is a significant difference of students’ critical thinking ability before and after using Jigsaw type. The other words, Jigsaw type was effective to increase students’ critical thinking ability by using Jigsaw type at the tenth grade students of TAV major of SMK Negeri 1 Batang Angkola.. Keywords: critical thinking ability, cooperative learning model of Jigsaw type